Enhanced removal of phosphate by hydrocalumite: synergism of AlPO4 and CaHPO4·2H2O precipitation. Issue 17 (8th April 2016) - Lu, Yongsheng; Hou, Hetian; Zhao, Jun; Zhou, Jizhi; Liu, Jianyong; Feng, Linlin; Qian, Guangren; Xu, Yunfeng
Abstract: In this work, the species of the precipitate after P removal in the solution was investigated. The characterization of calcined precipitates indicated that CaHPO4 ·2H2 O (DCPD) and AlPO4 were the predominant phosphorous precipitates at pH 5.0; the phosphorous removal was attributed to the formation of Ca5 (PO4 )3 OH (HAP) at pH 11.0. Additionally, AlPO4, DCPD, and HAP were formed in the neutral condition. This revealed that both Ca and Al in hydrocalumite were responsible for P removal. Correspondingly, based on the composition analysis, the molar ratio of (Ca + Al)/P in the extractable phosphorous precipitates increased from 1.05 to 2.21 with the increasing pH values. The results demonstrated that the phosphorous removal efficiency was reduced as the species evolution of Ca and Al precipitates. This work therefore proposed that lower pH promoted the phosphorous removal efficiency by Ca and Al consumption in LDH.